Pelatihan Pengisian Instrumen Akreditasi Pada Satuan PAUD di Kabupaten Kupang - Efraim Semuel Nalle; Retno Jeki Krisnadina Lopo; Rebeka Filda Hawali; Petrus Logo Radja; Anita A Hege Udju (Sekolah Tinggi Teologi Real Batam, 2023)
The purpose of early childhood education is to provide basic concepts that have meaningfulness for children through real experiences that allow children to show optimal activity and curiosity, therefore the need for a quality PAUD unit is evidenced by being accredited by the PAUD unit by the National Accreditation Board. The problems that occur in the PAUD unit have not been accredited because educators and managers do not know the instruments and documents that must be prepared, the management of institutional management has not been organized and learning planning has not been thoroughly understood and has not been properly arranged. The methods used in the implementation of the program are providing socialization of the 2013 curriculum, providing training on the preparation of learning implementation plans in PAUD and providing training on filling out accreditation instruments to educators and managers. From the results of the activities, participants were not only able to understand the 2013 PAUD curriculum but were able to design a learning implementation plan correctly. Participants are also able to upload documents based on these eight standards online because the application for PAUD accreditation is carried out centrally only online at SISPENA, to log in using the password owned by each PAUD. By understanding the curriculum and planning of learning programs as well as accredited status, the community can entrust early childhood to be educated or schooled in these schools.Keywords: accreditation; training; socialization AbstrakTujuan pendidikan anak usia dini adalah memberikan konsep-konsep dasar yang memiliki kebermaknaan bagi anak melalui pengalaman nyata yang memungkinkan anak untuk menunjukkan aktivitas dan rasa ingin tahu secara optimal, oleh karena itu diperlukannya satuan PAUD yang berkualitas dibuktikan dengan terakreditasi satuan PAUD oleh Badan Akreditasi Nasional. Permasalahan yang terjadi di satuan PAUD belum terakreditasi karena pendidik dan pengelola belum mengetahui instrumen dan juga dokumen-dokumen yang harus dipersiapkan, manajemen pengelolaan lembaga belum tertata dan perencanaan pembelajaran belum dipahami secara menyeluruh serta belum tersusun dengan baik. Metode yang digunakan dalam pelaksanaan program adalah memberikan sosialisasi kurikulum 2013, memberikan pelatihan penyusunan rencana pelaksanaan pembelajaran di PAUD dan memberikan pelatihan tentang pengisian instrumen akreditasi pada pendidik dan pengelola. Dari hasil kegiatan peserta tidak hanya mampu memahami kurikulum 2013 PAUD tetapi dapat merancang rencana pelakasanaan pembelajaan dengan benar. Peserta juga mampu mengunggah dokumen-dokumen berdasarkan delapan standar tersebut secara online karena pengajuan akreditasi PAUD dilaksanakan terpusat hanya dengan online di SISPENA, untuk login menggunakan password yang dimiliki oleh masing-masing PAUD. Dengan memahami kurikulum dan perencanaan program pembelajaran serta status terakreditasi baik masyarakat dapat mempercayakan anak usia dini dididik atau disekolahkan di sekolah-sekolah tersebut.Kata Kunci: akreditasi; pelatihan; sosialisasi